Group centered leadership - "Gordon, Thomas" (Boston, 1955)
This book actually began as a brief monograph describing one such experience. Those of us who had observed first-hand a certain group's development felt strongly that we should share our experience with others. In the process of trying to describe the experience, however, it soon became apparent that what happened to the group was not the entire there was also a philosophy and a theoretical rationale that story emerged more clearly as we, the leaders, planned our approach to the group. And even the process of planning itself became something we wanted to communicate, for we saw that this too was an important part of the story of the group's later development.
Keywords: Leadership